The effects of a very low-energy ketogenic therapy on body composition, gut microbiota and metabolites in overweight subjects - Khazrai, Yeganeh Manon; Di Rosa, Claudia; Altomare, Annamaria; Giovanetti, Marta; Di Francesco, Ludovica; Lattanzi, Greta; Spiezia, Chiara; Simone, Antonella; Coccaro, Federica; Costa, Giulia; Guarino, Michele Pier Luca; Manfrini, Silvia (Frontiers in Nutrition, 2026)
Obesity is associated with chronic diseases and gut-brain axis disruptions, with diet influencing gut microbiota. This single-arm, uncontrolled study evaluated the effects of a 28 – day Very Low-Energy Ketogenic Therapy (VLEKT) on body weight, gut microbiota, and stool-derived metabolites in individuals with excess weight. Forty-one subjects underwent baseline (T0) assessment including anthropometry, bioimpedance analysis, gut microbiota profiling and completed FAST questionnaire before and after 28 days of VLEKT with meal replacements (T1). Follow-up was conducted at T1. Thirty-one participants completed the intervention (T1). Results showed significant reductions in body weight, BMI, and fat mass. Microbiota analysis revealed decreased Firmicutes and Actinobacteria, and increased Bacteroidetes and Verrucomicrobia. Genus-level changes included increases in Bacteroides, Parabacteroides, and Akkermansia, and decreases in Streptococcus, Dorea, Blautia, Bifidobacterium, and Ruminococcus. Stool metabolites showed decreased butyrate and lactate and increased propionate, vitamin K2, and GABA. Because the study lacked a control group and did not include systemic biomarkers or biochemical confirmation of ketosis, microbiota and metabolite changes cannot be linked to physiological effects. Overall, findings indicate short-term weight loss and stool microbiota modulation, but all microbiota-related outcomes remain exploratory due to the small sample size, short duration, and uncontrolled design.